Running with horizontal pulling forces: the benefits of towing - Grabowski, A. M.; Kram, R. (European Journal of Applied Physiology, 2008)
Towing, or running with a horizontal pulling force, is a common technique used by adventure racing teams. During an adventure race, the slowest person on a team determines the team`s overall performance. To improve overall performance, a faster runner tows a slower runner with an elastic cord attached to their waists. Our purpose was to create and validate a model that predicts the optimal towing force needed by two runners to achieve their best overall performance. We modeled the effects of towing forces between two runners that differ in solo 10-km performance time and/or body mass. We calculated the overall time that could be saved with towing for running distances of 10, 20, and 42.2-km based on equations from previous research. Then, we empirically tested our 10-km model on 15 runners. Towing improved overall running performance considerably and our model accurately predicted this performance improvement. For example, if two runners (a 70 kg runner with a 35 min solo 10-km time and a 70-kg runner with a 50-min solo 10-km time) maintain an optimal towing force throughout a 10-km race, they can improve overall performance by 15%, saving almost 8 min. Ultimately, the race performance time and body mass of each runner determine the optimal towing force.